2022
DOI: 10.1093/brain/awac177
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the genetic architecture of cognitive resilience to Alzheimer’s disease

Abstract: Approximately 30% of elderly adults are cognitively unimpaired at time of death despite presence of Alzheimer’s disease (AD) neuropathology at autopsy. Studying individuals who are resilient to the cognitive consequences of AD neuropathology may uncover novel therapeutic targets to treat AD. It is well-established that there are sex differences in response to AD pathology, and growing evidence suggests that genetic factors may contribute to these differences. Taken together, we sought to elucidate sex-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 80 publications
3
36
1
Order By: Relevance
“…TSHZ1 is also essential for olfactory bulb development and olfaction ( Ragancokova et al, 2014 ). Further, GATA3, a transcription factor crucial in the differentiation of Th2 cells, was identified as a female-specific gene of AD implicated in RNA processing ( Eissman et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TSHZ1 is also essential for olfactory bulb development and olfaction ( Ragancokova et al, 2014 ). Further, GATA3, a transcription factor crucial in the differentiation of Th2 cells, was identified as a female-specific gene of AD implicated in RNA processing ( Eissman et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the pathway analysis, some transcription factors are associated with insulin signaling. For example, CREB3, STAT1, and STAT3 are important regulators of glucose and lipid metabolism in models of high-fat diet and obesity (Bone et al, 2020;Yao et al, 2021;Kiran et al, 2022;Opazo-Rios et al, 2022;Smith et al, 2022). In the context of neurodegeneration, CREB3 and STAT3 are involved in neuroprotective mechanisms.…”
mentioning
confidence: 99%
“…Fourth, a challenge to studying sex differences in AD is that women are more likely than men to survive to older ages. 3 When a gene, such as APOE , has pleiotropic effects on risk for mortality and AD, 49 this survival bias can cause spurious associations. Finally, given the rarity of APOE ε2 homozygosity, we were unable to investigate sex differences in allelic dose effects.…”
Section: Discussionmentioning
confidence: 99%
“…Neurological examination findings in AD (AD-NEF) from mutation carriers and non-carriers from the Dominantly Inherited Alzheimer Network (DIAN) revealed that AD-NEF are associated with a rapid cognitive decline and higher hippocampal atrophy [ 22 ]. Sex differences in the genetic make-up of resilience and multiple sex-specific molecular mechanisms may underlie resilience to AD pathology [ 23 ]. Perimenopausal and postmenopausal women aged 40 to 60 had more AD endophenotype than premenopausal women [ 24 ].…”
Section: Introductionmentioning
confidence: 99%